Financial Literacy and Assistance in Compiling Independent Financial Reports Using Expense IQ Money Manager - Arman, Andi; Mira, Mira; Masrullah, Masrullah; Agustan, Agustan; Firmansyah, Firmansyah; Aditya, Rahmat (Technium Sustainability, 2023)
Indonesia has a financial literacy rate far below average when compared to other countries that are members of ASEAN countries. Likewise, Thailand has a financial literacy score of 27 which is lower than the regional average, although the level of financial inclusion is quite high. The priority targets for financial literacy in 2023 will be allocated to the community, one of which is for students. Especially for students, knowledge of financial literacy will be built through the role of teachers as educators. Before being able to disseminate, of course, teachers need to first improve their understanding regarding their financial literacy. This can also be useful for teachers personally in managing their finances. The main problems of Eakapapsasnawich Islamic School Thailand School Teachers lie in the low level of financial literacy so they tend to make wrong decisions, lack of awareness in understanding the importance of recording their personal finances, and the absence of socialization about the use of financial software or financial recording applications in managing finances well, inspiring the Team to educate Eakapapsasnawich Islamic School Thailand School Teachers related to financial literacy and assistance in preparing independent financial statements using Expense IQ Money Manager. The method used is the provision of material through lectures, motivation, discussion, and practice / mentoring. The output target of this program is scientific articles published through service journals indexed by Sinta, and increasing teachers’ financial literacy in using digital-based financial recording applications.